Baboon endogenous virus genome. I. Restriction enzyme map of the unintegrated DNA genome of a primate retrovirus. - Cohen, M (1980)
A detailed restriction map was deduced for the genome of an endogenous retrovirus of a higher primate, that of baboon. The cleavage sites for 12 restriction enzymes were mapped. The unintegrated linear viral DNA intermediate that is produced by infection of permissive cells with baboon endogenous virus was isolated. Hybridization with a strong-stop complementary DNA probe demonstrated presence of a terminal repetition in the linear viral DNA. The positions of restriction sites for two particular enzymes, SmaI and XhoI, near each end were consistent with this result and indicated that the length of the repetition is 0.55 +/- 0.01 kilobase. The linear viral DNA had a unique restriction map indicating that it is not a set of random circular permutations of the RNA genome. From hybridization with a 3'-specific probe, the DNA restriction map was aligned relative to the 5'-to-3' orientation of the viral RNA. We observed a minor heterogeneity in a BamHI recognition site 1.95 kilobases from the right end of the linear map.